2004
DOI: 10.1111/j.0013-9580.2004.07903.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Surgery in Mesial Temporal Lobe Epilepsy: A Prospective Multicenter Study

Abstract: Summary:Purpose: This article is the first prospective documentation of the efficacy and safety of gamma knife surgery (GKS) in the treatment of drug-resistant epilepsies of mesial temporal lobe origin.Methods: From July 1996 to March 2000, three European centers selected 21 patients with mesial temporal lobe epilepsy (MTLE) for a temporal lobectomy. The preoperative investigations included video-EEG with foramen ovale electrodes, magnetic resonance imaging, neuropsychological testing, and the ESI-55 quality-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
193
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(207 citation statements)
references
References 64 publications
(91 reference statements)
11
193
1
2
Order By: Relevance
“…62.5% of patients were treated with propofol; 28.8% with thiopental and 9.6% with propofol and subsequently with thiopental. Median duration of ICU stay was 3.34 days (range [1][2][3][4][5][6][7][8][9][10][11][12]. Twenty-nine patients survived the episode of RSE; 2 patients died and 1 patient is in a persistent vegetative state due to cerebrovascular complications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…62.5% of patients were treated with propofol; 28.8% with thiopental and 9.6% with propofol and subsequently with thiopental. Median duration of ICU stay was 3.34 days (range [1][2][3][4][5][6][7][8][9][10][11][12]. Twenty-nine patients survived the episode of RSE; 2 patients died and 1 patient is in a persistent vegetative state due to cerebrovascular complications.…”
Section: Resultsmentioning
confidence: 99%
“…They were examined at the in-and outclinic between 1987 and 2000, and were followed-up for mean 4.5 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The schemes of diagnostic criteria (inclusion to an epileptic syndrome and criteria of exclusion from one) were worked up according to ILAE (1989) and Proposed Diagnostic Scheme for People with Epileptic Seizures and with Epilepsy (2001), and other published data.…”
Section: P782 Syndromic Classification In Childhood-onset Epilepsymentioning
confidence: 99%
“…3) Delay in seizure control after GKRS for MTLE has been well documented. [2][3][4]11,24) Significant reduction in seizures usually occurred at least 1 year after GKRS. Delayed treatment response makes evaluation of the treatment effectiveness difficult, because some patients might undergo open surgery before seizure control by GKRS.…”
Section: Discussionmentioning
confidence: 99%
“…GKRS for MTLE using 24 Gy resulted in seizure-free rate of 60% after 6-10 years follow-up. 3,24) Another pilot study reported that 67% of patients with MTLE were seizure-free after GKRS using 20 or 24 Gy at the 36-month followup evaluation. 2) However, some studies reported that none of the patients became seizure-free after GKRS.…”
Section: Introductionmentioning
confidence: 99%
“…The same researchers then initiated a multicenter study, which was conducted at 3 European centers. 57 Twenty patients underwent radiosurgery with 24-25 Gy delivered to the mesial temporal lobe for intractable mesial temporal lobe epilepsy. After a follow-up period of 2 years, 65% of these patients were seizure free, however, it took about 12 months postsurgery for the seizure frequency to begin to drop significantly.…”
Section: Mesial Temporal Lobe Epilepsymentioning
confidence: 99%